2004
DOI: 10.1097/00006254-200407000-00024
|View full text |Cite
|
Sign up to set email alerts
|

HPV Testing and Monitoring of Women After Treatment of CIN 3: Review of the Literature and Meta-analysis

Abstract: According to the current guidelines in most western countries, women treated for cervical intraepithelial neoplasia grade 3 (CIN 3) are followed for at least 2 years after treatment by cytology.High-risk human papillomavirus (hrHPV) infections are necessary for the development and maintenance of CIN 3. HrHPV testing could be used to improve monitoring of women treated for CIN 3. This has prompted numerous studies for the implementation of hrHPV testing in monitoring of women treated for CIN 3. Included in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
101
0
11

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 36 publications
10
101
0
11
Order By: Relevance
“…2) and almost 70% of patients had both tests negative, which corresponds to results of other studies (14). Given the high sensitivity and concordance in our results we conclude that in our setting (with poorer resources and high quality cytology) it is not cost-effective to perform both tests to all women after conization.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…2) and almost 70% of patients had both tests negative, which corresponds to results of other studies (14). Given the high sensitivity and concordance in our results we conclude that in our setting (with poorer resources and high quality cytology) it is not cost-effective to perform both tests to all women after conization.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have shown that combined testing has the highest sensitivity in detecting a residual/recurrent disease [14]. According to our results both tests show a very good performance in detecting a residual/recurrent disease so depending on the socio-economic aspect both can be used as a primary follow-up tool after conization.…”
Section: Discussionmentioning
confidence: 62%
“…A meta-analysis of Zielinski et al showed that the status of excision margins, posttreatment cytology, post-treatment hr-HPV or combinations had a negative predictive value of 91-99%, the positive predictive values of these parameters were 25-51% [17]. Based on this study they proposed to follow-up patients with negative cytology in combination with negative hr-HPV DNA testing less intensively.…”
Section: Discussionmentioning
confidence: 99%
“…HPV testing picks up residual disease quicker with higher sensitivity and similar specificity to cytology. Zielinski has proposed combined cytology and HPV testing at 6 and 24 months after treatment and referral back to 5 years cytology screening if all tests are negative 29 .…”
Section: Risk Factors For Hpv Infection and Neoplasiamentioning
confidence: 99%